RISK FACTORS OF STUNTING EVENTS IN TODDLERS AGED 24-59 MONTHS - Mufidah Binti Eka; Ilya Krisnana; Dominicus Husada (UNIVERSITAS AIRLANGGA, 2020)
AbstractBackground: Stunting is one priority problem in Indonesia. The incidence of stunting in toddlers at the Tambak Wedi Public Health Center Surabaya in 2015 and 2016 were 31.3% and 33%, respectively. This study aims to analyze the risk factors for stunting in toddlers aged 24-59 months in Tambak Wedi Health Center Surabaya. Method: This observational analytic research used cross sectional approach. The population in this study was 220 and the sample size was 110 mothers and toddlers. Samples were selected by proportional cluster random sampling from the population of 220 pairs mothers and toddlers. Independent variables of the mothers include height, upper arm circumference, frequency of ANC visits, weight gain during pregnancy, meanwhile of the toddlers included birth length and birth weight. The dependent variable was stunting. Statistical analysis used chi-square and multiple logistic regression tests. Results: There were 100 pairs of mother and toddlers in the study. Bivariate analysis showed a significant relationship between maternal height (p = 0.025, RR = 0.406), frequency of ANC visits (p = 0.017, RR = 0.382), increase in maternal weight during pregnancy (p = 0.017, RR = 0.328), the baby’s birth length (p = <0.001, RR = 0.256), and the baby's birth weight (p = <0.001, RR = 0.208) with stunting. Multivariate analysis showed maternal height and ANC visit as the significant risk factors of stunting. Conclusion: Maternal height and the frequency of ANC visits were the risk factors for stunting among toddlers aged 24-59 months in Tambak Wedi Public Health Center in Surabaya.